Attitudinal evaluations in two versions of research articles: A cross-linguistic exploration of their pattern shifts - Wenchao Zhao (Ibérica)
Attitudinal evaluations have long been of interest to researchers of academic discourse. Yet, much research on the linguistic phenomena has been carried out with reference to first or second language users’ English academic writings. Cross-linguistic studies are seldom undertaken in relation to the coupling patterns of attitudinal evaluations and their variations in different academic languages. Designed as mixed-methods research, this study investigates attitudinal evaluations in a collection of research articles published in both Chinese and English versions, exploring how evaluative coupling patterns shift cross-linguistically in terms of the systemic functional ideas of attitudinal evaluation and coupling. Findings show that while some cross-linguistic coupling pattern shifts normally occur with the evaluated targets remaining unchanged, some others usually appear with concomitant target change. Importantly, the study reveals that some coupling pattern shifts stand out by displaying lexicogrammatical delicacy variations in representing evaluative meaning or exhibiting what may be called a cross-linguistic metaphoric shift towards thingness. It was argued that the study adds to the picture of different approaches to evaluative language and offers a heuristic for characterizing cross-linguistic rhetorical variations and teaching languages for academic purposes, especially to students with Chinese or English as the foreign or second language.